A probabilistic definition of a species, fuzzy boundaries and 'sigma taxonomy' - Schrein, C.M.; Thackeray, J.F. (Academy of Science of South Africa (ASSAF)., 2017)
No abstract available.
Keywords: Alpha taxonomy; Biological species constant; Genetic analysis; Hybridisation; Morphometric analysis